Housekeeping proteins: How useful are they in skeletal muscle diabetes studies and muscle hypertrophy models? - Fortes, M.; Marzuca-Nassr, G.; Vitzel, K.; Da Justa Pinheiro, C.; Newsholme, Philip; Curi, R. (Academic Press, 2016)
The use of Western blot analysis is of great importance in research, and the measurement of housekeeping proteins is commonly used for loading controls. However, Ponceau S staining has been shown to be an alternative to analysis of housekeeping protein levels as loading controls in some conditions. In the current study, housekeeping protein levels were measured in skeletal muscle hypertrophy and streptozotocin-induced diabetes experimental models. The following housekeeping proteins were investigated: glyceraldehyde-3-phosphate dehydrogenase (GAPDH), β-actin, α-tubulin, γ-tubulin, and α-actinin. Evidence is presented that Ponceau S is more reliable than housekeeping protein levels for specific protein quantifications in Western blot analysis.